Residential radon and environmental burden of disease among Non-smokers. Issue 1 (December 2016) - Noh, Juhwan; Sohn, Jungwoo; Cho, Jaelim; Kang, Dae; Joo, Sowon; Kim, Changsoo; Shin, Dong
Abstract Background Lung cancer was the second highest absolute cancer incidence globally and the first cause of cancer mortality in 2014. Indoor radon is the second leading risk factor of lung cancer after cigarette smoking among ever smokers and the first among non-smokers. Environmental burden of disease (EBD) attributable to residential radon among non-smokers is critical for identifying threats to population health and planning health policy. Methods To identify and retrieve literatures describing environmental burden of lung cancer attributable to residential radon, we searched databases including Ovid-MEDLINE, -EMBASE from 1980 to 2016. Search terms included patient keywords using 'lung', 'neoplasm', exposure keywords using 'residential', 'radon', and outcomes keywords using 'years of life lost', 'years of life lost due to disability', 'burden'. Searching through literatures identified 261 documents; further 9 documents were identified using manual searching. Two researchers independently assessed 271 abstracts eligible for inclusion at the abstract level. Full text reviews were conducted for selected publications after the first assessment. Ten studies were included in the final evaluation. Review Global disability‐adjusted life years (DALYs)(95 % uncertainty interval) for lung cancer were increased by 35.9 % from 23, 850, 000(18, 835, 000-29, 845, 000) in 1900 to 32, 405, 000(24, 400, 000-38, 334, 000) in 2000. DALYs attributable to residential radon were 2, 114, 000(273, 000-4, 660, 000) DALYs in 2010. Lung cancer caused 34, 732, 900(33, 042, 600 36, 328, 100) DALYs in 2013. DALYs attributable to residential radon were 1, 979, 000(1, 331, 000-2, 768, 000) DALYs for in 2013. The number of attributable lung cancer cases was 70-900 and EBD for radon was 1, 000-14, 000 DALYs in Netherland. The years of life lost were 0.066 years among never-smokers and 0.198 years among ever-smoker population in Canada. Conclusion In summary, estimated global EBD attributable to residential radon was 1, 979, 000 DALYs for both sexes in 2013. In Netherlands, EBD for radon was 1, 000–14, 000 DALYs. Smoking population lost three times more years than never-smokers in Canada. There was no study estimating EBD of residential radon among never smokers in Korea and Asian country. In addition, there were a few studies reflecting the age of building, though residential radon exposure level depends on the age of building. Further EBD study reflecting Korean disability weight and the age of building is required to estimate EBD precisely.